How is physical healthcare experienced by staff, service users, and carers in adult community mental health services in a south London mental health trust? A service evaluation - Tredget, Gracie; Williams, Julie; McGrath, Ray; Sadler, Euan; Gaughran, Fiona; Ang, Karen; Stepan, Natalia; Cross, Sean; Tweed, John; Orlando, Lia; Sevdalis, Nick; , the Integrating our Mental; et al. (Frontiers in Health Services, 2023)
Background Adults with a serious mental illness (SMI) are at greater risk of physical health morbidity and premature death than the general population, largely as a result of preventable physical health issues. Staff working in mental health services have a role to play in addressing these inequalities, but little is known about how they perceive their role and how this impacts on their practice. Understanding this better would enable services to improve their approach and support better health outcomes for SMI patients. A service evaluation was undertaken to investigate how physical healthcare is approached within adult community mental health teams (CMHTs) at a South London (UK) Mental Health Trust. Methods This was a prospective, cross-sectional evaluation design. Interviews and focus groups were conducted with clinical staff, service users and carers (non-professional caregivers e.g., family or friends, of adults living with an SMI), to understand their experiences and to identify key barriers and facilitators to supporting physical healthcare support for adults with SMI. Thematic analysis was conducted to identify key themes which were classified into five main categories. Results 50 participants took part in the study, 38 were clinical staff, eight were service users and four were carers. We found staff widely recognised the importance of supporting physical healthcare. However, there was variability in how staff approached physical healthcare in routine practice, and differences in how physical healthcare is experienced by service users and carers. Staff were keen to engage in changes to the way physical healthcare is delivered in CMHTs. However, they sought clearer guidance on their roles and responsibilities, and wanted to better understand the rationale for changes in community mental health practice, such as increased screening for physical healthcare. Service users and carers felt equally that the role of CMHTs in physical healthcare was unclear, which limited their ability to access it and understand the benefit for their overall care. Staff articulated gaps in leadership and training that impacted on their ability to implement the overall vision for physical healthcare within the Trust. Conclusion Mental health staff recognise the role they play in supporting the physical health of adults living with SMI. This evaluation provides insight into common barriers and facilitators faced by staff, service users and carers when providing or accessing physical healthcare within adult CMHTs. These findings indicate a more comprehensive and better articulated approach to physical healthcare in mental health Trusts is needed to ensure service users and their carers understand what support is available and how to access it and to equip staff to provide and sustain that care in routine practice.